The neural basis underlying the association between parents’ socioeconomic status and depressive symptoms among college students - Xiao, Yao; Jiang, Xinting; Li, Yuan; Mao, Yu; Zhou, Duyi (Frontiers in Psychology, 2024)
Depression is increasingly prevalent among adolescents, with parents' socioeconomic status (SES) serving as significant predictors. Understanding the link between parents' SES and college students' depressive symptoms is of paramount concern. However, the neural basis linking the association between parents' SES and students' depressive symptoms still remains to be explored. In order to address this issue, this study aims to investigate the relationship between parents' SES and students' depressive symptoms, and the role of brain functional connectivity (FC) pattern in this relationship. In this study, a total of 363 college students without a history of mental or neurological disorders underwent depressive symptoms assessment and resting-state functional magnetic resonance imaging scans. We used a connectome-based predictive modeling (CPM) approach to identify neural biomarkers of depressive symptoms. The results indicate that there is a negative correlation between parents' SES and students' depression tendencies(Father' s education level and SDS:r =-0.119, p <0.05; Mother' s education level and SDS:r=-0.117, p <0.05), suggesting that students whose parents have a higher educational level are less likely to suffer from depression.Furthermore, a FC pattern that can significantly predict depressive symptoms outside of the body was identified(r=-0.13, P <0.005), with most of the FCs belonging to the default mode network (DMN) and ventral attention network (VAN). Additionally, the FC pattern associated with depressive symptoms mediate the relationship between parents' SES and depressive symptoms. Therefore, we believe that improving the education levels of parents may have a practical effect in reducing depressive symptoms among adolescents.